TELAAH UTANG PIUTANG PERSPEKTIF ISLAM DAN PINJOL - Niskaromah, Niskaromah (Bajang Institute, 2024)
Debt is one solution to economic problems that is permitted in Islamic law. Refering to Q.S. al-Mâidah [5]: 2 debt is based on a relationship of mtual help, therefore debt is free of interest (riba). Islam provides provisions regarding debt that must be obeyed (Q.S. al-Baqarah [2]: 282). Several Hadith texts also provide information about threats aimed at people who owe money (muqtariḍ) but do not intend to pay. On the other hand, people who give debts (muqriḍ) there is a recommendation to always be lenient and tolernt in collecting debts. Developments in the field of information technology have also shifted previously conventional debt and receivable transactions to Financial Technology (Fintech) or pinjol. Based on the principles of Islam, this system is permissible according to Islamic law. Pinjol appeared in 2016, and with OJK Regulation Number 77/PJOK.01/2016 and Bank Indonesia Regulation Number 19/12/PBI/2017, Pinjol's status is legal. Since its appearance, pinjol has grown massively and is a trend in society. This is because this loan service provides very easy requirements and can be accessed easily too. Viewed from a positive perspective, pinjol is considered capable of boosting the Indonesian economy, but it contains an element of interest (riba). From a negative perspective, pinjol has high interest, especially fines for late payment. This research will discuss about debts or called al-Qarḍ and debts of the fintech P2P lending version or pinjol, using the ushul rule approach: كل قرض جرّمنفعة فهو ربا. This research is library research where data is obtained from various literature in accordance with the research object; books, journals and other accurate data. Through descriptive analysis, the comparison between the two debts models is intended to provide an understanding of the fundamental differences between them. The research results show that debt (القرض) is based on the principle of mutual assistance (التعاون) therefore it does not contain the element of riba. Pinjol is legal, but the legality does not necessarily make this transaction halal, based on Islamic law rules كل قرض جرّمنفعة فهو ربا.